Integrated Weed Management in Golf Courses and Recreational Areas - Lee, S.A. (INTI Publishing House Sdn Bhd, 2005)
This paper provides an updated list of major weeds in some golf courses, recreation gardens, parks and football fields in Kuala Lumpur, Petaling Jaya, Shah Alam and Kampung Kuantan, Selangor from 1994 to 2004. Many broadleaf weeds, grasses and sedges are recorded, particularly in the roughs, collars and fairways of golf courses. In general, more weeds were observed on golf courses planted with Bermuda grass/Serangoon grass than carpet grass (Axonopus compressus). In golf courses, some of the major weeds of fairways are Borreria latifolia, Lindernia spp., Desmodium sp., Axonopus compressus (a weed on fairways and aprons which have Serangoon grass or Bermuda grass), Chrysopogon aciculatus, Digitaria fuscescens, Eleusine indica, Paspalum conjugatum, Paspalum vaginatum, Cyperus brevifolius, Cyperus rotundas and Fimbristylis miliacea. In recreation parks and football fields where carpet grass (Axonopus compressus) is the major turf species cultivated, the major weeds include Asystasia gangetica, Borreria spp., Desmodium sp. Cleome spp., Euphorbia hirta, Mimosa pudica, Eleusine indica, Imperata cylindrica, Cyperus app., and Fimbristylis miliacea. In waterlogged areas, Panicum repens, Cyperus aromaticus, Cyperus brevifolius and Fimbristylis miliacea tend to dominate. Integrated weed management (IWM) must start at the pre-planting stage and there should be a long-term action plan to manage the weeds in the turf itself and in its vicinity since weeds spread from their seeds, tubers, rhizomes and fragments. IWM includes preventive, cultural and mechanical approache8. Frequent mowing is the most popular method used in golf courses and sports fields, and it is in line with holistic management of turf grasses today. Chemical control and biological approaches are also discussed, a list of 26 foreign weeds to watch is included as some of them may be capable of establishing a foothold in turf grasses in Malaysia.